Performance test of the gripper control system on a robot arm for picking tomatoes - Saputra, Oki; Wahyudi, Wahyudi; Sumarsono, Joko; Setiawati, Diah Ajeng; Dewi, Endang Purnama (Universitas Muhammadiyah Mataram, 2024)
As the demand for precision agriculture intensifies, the integration of robotics into crop harvesting processes becomes imperative. This study addresses the design and evaluation of a gripper specifically tailored for a robotic arm, aiming to enhance the efficiency of tomato harvesting. The gripper is meticulously crafted, employing a 3 mm plywood material and subjected to rigorous testing at variable angles of 40°, 45°, and 50°. The design process initiates with a meticulous blueprint and laser printing, utilizing 3 mm plywood to create a robust gripper structure. Experimental trials are conducted to assess the gripper's performance under different angle configurations. The results reveal an exemplary success rate, with a 100% achievement in the successful transfer of tomatoes without incurring any damage. The gripper's adaptability to variable angles proves crucial in maintaining. the integrity of tomatoes during the harvesting process. Furthermore, data analysis encompasses crucial parameters such as gripping time, torque exerted by the gripper, and the percentage of tomatoes successfully transferred Testing results reveal a gripping time of 0.14 seconds, indicating an efficient gripper with the highest torque at a 40° angle. The detailed design and adaptive nature of the gripper hold promise as precision technology for tomato harvesting, contributing to discussions on the integration of robotics in agriculture, particularly in optimizing harvests. Future recommendations include enhancing the gripper's structural materials for increased durability and incorporating pressure sensors to further refine its capabilities